1965
DOI: 10.1099/00221287-38-3-309
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline Phosphatase in Dictyostelium discoideum

Abstract: SUMMARYSeveral phosphatases have been demonstrated in Dictyostelium discoideum. The alkaline phosphatase, pH optimum 9.0, is a 5'-nucleotidase, attacking adenosine monophosphate and deoxyadenosine monophosphate, but catalyses also hydrolysis of p-nitrophenyl phosphate. In the absence of exogenous nutrients this enzyme increases about 6-fold in vitro during differentiation. Its activity\in vivo may in part be controlled through endproduct inhibition by orthophosphate which has been found to accumulate in the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

1968
1968
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Several years ago, Gezelius and Wright reported differential instability of alkaline phosphatase extracted from vegetative amoebae, preculmination cells and sorocarps [9]. Enzyme from vegetative cells retained only ten percent of its activity when cell-free extracts were stored for X days at 4°C while from preculmination cells and sorocarp cells retained 29% and 50% of the initial activity respectively under identical conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Several years ago, Gezelius and Wright reported differential instability of alkaline phosphatase extracted from vegetative amoebae, preculmination cells and sorocarps [9]. Enzyme from vegetative cells retained only ten percent of its activity when cell-free extracts were stored for X days at 4°C while from preculmination cells and sorocarp cells retained 29% and 50% of the initial activity respectively under identical conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In this connection, it is noteworthy to recall that D. discoideum spores contain 65 mM inorganic phosphate. 7 ) We had analyzed and reported some of the chemical nature of the SGPs. 9 ) The data from these experiments also confirmed 'most of the characteristics of the SGPs such as heat stability and enzyme digestion.…”
Section: Discussionmentioning
confidence: 99%
“…The 5NT activity showed an alkaline pH optimum, and like ALP in other systems, was able to degrade the artificial substrate p-nitrophenyl phosphate (pNPP) (Gezelius and Wright, 1965). When the protein containing 5ЈAMP degrading activity was purified to homogeneity it was found that both 5ЈAMP and pNPP could be utilized as a substrate, but that the enzyme showed a high preference for 5ЈAMP over any other natural products.…”
mentioning
confidence: 98%
“…In Dictyostelium a phosphatase activity exhibiting an alkaline pH optimum and a substrate preference for 5ЈAMP has been the subject of study by several laboratories (Armant and Rutherford, 1981;Weeks, 1985, 1989a,b;Cladaras et al, 1983;Das and Weeks, 1980Gezelius and Wright, 1965;Glomp et al, 1985;Krivanek, 1956;Loomis, 1969;MacLeod and Loomis, 1979;O'Day and Francis, 1973;Parish and Pelli, 1974;Tisa and Cotter, 1979). Assays of the phosphatase activity have utilized artificial substrates as well as 5ЈAMP.…”
mentioning
confidence: 98%